Comparison of anti-VEGF therapies on fibrovascular pigment epithelial detachments in age-related macular degeneration. Issue 7 (2nd December 2016) - Au, Adrian; Parikh, Vishal S; Singh, Rishi P; Ehlers, Justis P; Yuan, Alex; Rachitskaya, Aleksandra V; Sears, Jonathan E; Srivastava, Sunil K; Kaiser, Peter K; Schachat, Andrew P; Martin, Daniel F; Modi, Yasha
Abstract : Background: The aim is to compare the therapeutic effects of three antivascular endothelial growth factor (VEGF) drugs (bevacizumab, aflibercept and ranibizumab) on fibrovascular pigment epithelial detachments (fvPEDs) in age-related macular degeneration (AMD). Methods: This was a retrospective, comparative, consecutive case series of 88 unique eyes with fvPEDs in neovascular AMD treated with anti-VEGF monotherapy for a minimum of 6 months. All eyes were treatment naive. Diagnosis was confirmed retrospectively by fluorescein angiography and spectral-domain optical coherence tomography. Exclusion criteria included serous/drusenoid PEDs or patients who switched anti-VEGF. Mean follow-up across all therapies was 313.9±85.3 days. Results: Average age of all patients was 80.6 years. Baseline maximum subfoveal PED height was 326.8±185.1 μm, 394.5±238.6 μm and 258.0±145.3 μm for bevacizumab, aflibercept and ranibizumab, respectively (p=0.05). All patients had subretinal fluid, intraretinal fluid or a combination of the two at an initial presentation. Central retinal thickness decreased at all time points compared with baseline across all three anti-VEGF therapies. Subfoveal PED height decreased in patients treated with aflibercept at all time points and decreased in patients treated with bevacizumab at 1-month, 3-month and 6-month time points. Aflibercept reduced PED height more than bevacizumab at 1-month and 12-month follow-ups (p=0.02 and p=0.03, respectively) and ranibizumab at 1-month and 6-month follow-ups (p=0.03 and p=0.02, respectively). No differences in best-corrected visual acuity were appreciated at any time point between drugs. Conclusions: There was a significant reduction in subfoveal PED height for aflibercept and bevacizumab compared with baseline. A direct comparison of drugs demonstrated a beneficial reduction of PED height, albeit inconsistently, favouring aflibercept. There were no differences in visual acuity across the groups at any time point.